Structural performance of a new blind-bolted frame modular beam-column connection under lateral loading - Cho, Bong Ho; Lee, Jae Sub; Kim, Hongjin; Kim, Dae Jin (Applied Sciences (Switzerland), 2019)
This study proposes an effective steel frame modular system and evaluates the structural performance of its beam-column connection through experimental and analytical work. The new steel frame modular system utilizes the blind bolts, which allow free access to the structural members of the closed cross-section. In addition, the new modular system is designed such that the strength of its beam members is considerably lower than that of its column members to implement the strong column-weak beam concept. In order to investigate the effectiveness of the proposed modular beam-column connection, two types of specimens were designed and tested. One of the two specimens has four knee brace members to increase the bending stiffness of the connection, while the other does not have these components. The applied load versus displacement curves are plotted for the two specimens, and their failure modes are identified. Finally, a simplified analytical model for the modular beam-column connection is proposed, and its effectiveness is validated by performing its push-over analysis and comparing its results with the test results.
Keywords: Beam-column connection; Hysteresis curve; Lateral loading; Steel modular building